Large Scale LEO Satellite Internet Routing Algorithm Based on Load Balancing - Yijie WANG; Wei ZHAO; Fei CHENG; Wen CHEN; Anjie CAO (天地一体化信息网络)
The expanding market demand has set off an upsurge of large-scale LEO constellation deployment.With the characteristics of large bandwidth, low delay and continuous coverage, it provides broadband internet services for users all over the world.Aiming at the problem of congestion and packet loss caused by uneven network load, an adaptive large-scale LEO inter satellite routing algorithm based on load balancing was proposed.The algorithm divided the direction and level of candidate satellites according to the information obtained from small area detection, calculated the weight value according to diff erent partition results, and selected the next hop node with the highest level and the lowest weight value, carry out the same steps hop by hop until the data reaches the destination satellite node, fi nally formed a low delay path to realized low packet loss rate data transmission in the whole network.Through the simulation experiment, compared with the classical algorithm and the existing large-scale LEO satellite routing algorithm, the routing algorithm could eff ectively improved the routing performance of LEO large-scale satellite communication network and provided high-quality services for users.